2022
DOI: 10.3390/math10244772
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid Launch Vehicle Safety Assessment Model Based on Semi-Quantitative Interval Belief Rule Base

Abstract: As the propulsion part of a space launch vehicle and nuclear weapon missile, the health status of the liquid rocket determines whether the space launch vehicle and nuclear weapon missile can function normally. Therefore, it is of great significance to evaluate the health status of the liquid rocket. As the structure of the liquid rocket is becoming increasingly sophisticated, subjective judgment alone can no longer meet the needs of the actual system. As an expert system and a gray-box model, the belief rule b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Kamal and Steven built a quantitative strategy based on the London stock market using the turtle trading rule, mainly from the optimization of the parameter settings for market entry, stop loss, position addition and market exit. The test results showed that the system with optimized parameters during the period from March 2007 to April 2007 had significant results [3].…”
Section: Literature Referencesmentioning
confidence: 99%
“…Kamal and Steven built a quantitative strategy based on the London stock market using the turtle trading rule, mainly from the optimization of the parameter settings for market entry, stop loss, position addition and market exit. The test results showed that the system with optimized parameters during the period from March 2007 to April 2007 had significant results [3].…”
Section: Literature Referencesmentioning
confidence: 99%